Bone Transport of Tibia - Omer Ali Rafiq Barawi; Zmnako J. Amen (European Scientific Journal, ESJ, 2018)
This is a comparative study to evaluate the outcome of forty patients with bone loss in tibia using conventional external fixation device for group A while for group B using Ilizarov external fixator device each group consists of 20 patients, based on principles of distractive osteogenesis. Patients and methods: Forty patients with bone loss of 4 to 14 centimeters in tibia between April 2011 and April 2016 were treated, ages (15-65 years); female to male ratio was 6:34. The cause of defects in tibia was fracture due to road traffic accident (20 cases), bullet injury to leg (8 cases), gap nonunion (8 cases) and infected non unions(4 cases). They were divided into two groups each consists of 20 patients, conventional external fixator used for group A while for group B Ilizarov external fixator device was used with performing transverse corticotomy proximal or distal to the gap for both groups. Results: Evaluation of results was done according to Association for Study and Application of Methods of Ilizarov (A.S.A.M.I.) scoring system and it revealed that both functional and bony results were better in group B than group A. Conclusions: Fixation of the bone by Ilizarov frame gives more rapid union of the bone, less chance of pin tract infection and cosmetically more preferable because of smaller scar tissue of entry of K wires than Schanz pins. Prevention and treatment of equinus deformity and clawing of the toes can be done by extending the Ilizarov frame to correct them. In cases of severe soft tissue loss it is better to apply conventional external fixator as a provisional fixator till the soft tissue loss and swelling will be diminished.